Implantação de ferramenta de análise preditiva: um estudo de caso - Pires, Renato De Luca (2017)
In a context of high competitiveness, it is natural that companies seek in Information Technology tools to assist in their search for better results and differentiation of their competitors. Often the information for this task can be retrieved from their current ERP systems, which has unused data for the benefit of the business. This research investigated through a single case study the impacts on the managerial processes of a company, resulting from the use of a business intelligence system with predictive capacity. After review reviewing the literature on management information systems from the 1950s to the present time, three propositions were elaborated in order to answer the research question. The first proposes that the business intelligence system has impacted the way the company's strategic planning occurs; and secondly, that the business areas have had an impact on the way they work, and the third, that the company's analytical culture facilitates the introduction of new technologies. The research data collection stage was carried out in a large multinational company, manufacturer of equipment for domestic use, leader in its sector of activity. The object of study was a new business intelligence system with newly deployed predictive capacity, and its effects on the strategic planning and business areas of the company. The conclusion is that the impact of the use of the system was positive, since there were gains from its use, such as better determination of product costs, as well as providing better information for the purchasing area to use in its negotiations.